Analisis Faktor Yang Mempengaruhi Keputusan Konsumen Di Hidden Strawberry Garden, Kabupaten Buleleng - Tarigan, Catherin Feronika; Hartiati, Amna; Suwariani, Ni Putu (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI, 2026)
Purchasing decisions in the agro-tourism sector are not only influenced by the quality of products in the form of fresh and processed strawberries, but also by price, place, promotion, people, process and physical evidence. This study aims to find out what factors affect consumer decisions, determine the dominant variables that represent each factor in influencing consumer decisions, and find out strategies to improve consumer decisions in Hidden Strawberry Garden, Buleleng Regency. The data collection technique in this study was carried out by distributing 85 questionnaires to respondents. The data obtained was then analyzed using factor analysis and processed using the SPSS version 30 program. The results obtained showed that the number of factors formed was 5 factors. Factor 1 (combination of people and processes) with an eigenvalue of 10,017 consisting of 6 variables, namely: the speed of employees in overcoming complaints, employee knowledge about agrotourism, employee attention to visitors, good and neat employee appearance, ease of communication, and the payment process is carried out quickly. Factor 2 (combination of products, physical evidence, and price) with an eigenvalue of 2,326 consisting of 8 variables, namely: product quality, good fruit quality, availability of strawberries, providing additional facilities such as relaxation areas and toilets, photo spot areas or special spots for visitors, parking lots, appropriate product selling prices, and a comfortable agrotourism atmosphere. Factor 3 (combination of promotions, people, products, and prices) with an eigenvalue of 1,831 consisting of 4 variables, namely: direct marketing, employee knowledge about agrotourism, product guarantees, and discounts. Factor 4 (combination of products and promotions) with an eigenvalue of 1,439 consisting of 4 variables, namely: variety of processed strawberry products, complete information on promotional media, products have attractive packaging, and product sizes vary. Factor 5 (combination of price and place) with an eigenvalue of 1,413 consisting of 4 variables, namely: an easy-to-reach agro-tourism location, a strategic agro-tourism location, a price that is easily accessible to all groups, and various product distribution channels available.